The first cell : and the human costs of pursuing cancer to the last - Raza, Azra (Basic Books, 2019)
We have lost the war on cancer. We spend $150 billion each year treating it, yet -- a few innovations notwithstanding -- a patient with cancer is as likely to die of it as one was fifty years ago. Most new drugs add mere months to one's life at agonizing physical and financial cost. In The First Cell, Azra Raza offers a searing account of how both medicine and our society (mis)treats cancer, how we can do better, and why we must. A lyrical journey from hope to despair and back again, The First Cell explores cancer from every angle: medical, scientific, cultural, and personal. Indeed, Raza describes how she bore the terrible burden of being her own husband's oncologist as he succumbed to leukemia. Like When Breath Becomes Air, The First Cell is no ordinary book of medicine, but a book of wisdom and grace by an author who has devoted her life to making the unbearable easier to bear.